Konsep Ketuhanan Filsafat Saiva Advaita - Ni Made Evi Kurnia Dewi; Komang Heriyanti (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Trust is an important element in understanding a religion,but trust is not enough to answer the question about God (Siva) logically.Saiva Advaita's philosophy is here to answer all questions about Lord Siva logically.